2015
DOI: 10.1093/pcp/pcv035
|View full text |Cite
|
Sign up to set email alerts
|

Iron Availability Affects Phosphate Deficiency-Mediated Responses, and Evidence of Cross-Talk with Auxin and Zinc in Arabidopsis

Abstract: Phosphate (Pi) is pivotal for plant growth and development. Pi deficiency triggers local and systemically regulated adaptive responses in Arabidopsis thaliana. Inhibition of primary root growth (PRG) and retarded development of lateral roots (LRs) are typical local Pi deficiency-mediated responses of the root system. Expression of Pi starvation-responsive (PSR) genes is regulated systemically. Here, we report the differential influence of iron (Fe) availability on local and systemic sensing of Pi by Arabidopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 92 publications
5
57
0
Order By: Relevance
“…The Mediator (MED) complex is a multi-subunit complex that acts as a bridge between promoter-bound transcription factors and the RNA polymerase II transcription initiation complex to control gene expression. In plants, MED subunits participate in several developmental processes, hormonal signaling pathways, and biotic and abiotic stress tolerance (Manners and Kazan, 2009;Gillmor et al, 2010Gillmor et al, , 2014Ito et al, 2011;Xu and Li, 2011;C ßevik et al, 2012;Rai et al, 2014;Yang et al, 2014;Zhang et al, 2014;Raya-Gonz alez et al, 2014. However, how MED subunits could be interacting to determine the MED functioning per se on plant development remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The Mediator (MED) complex is a multi-subunit complex that acts as a bridge between promoter-bound transcription factors and the RNA polymerase II transcription initiation complex to control gene expression. In plants, MED subunits participate in several developmental processes, hormonal signaling pathways, and biotic and abiotic stress tolerance (Manners and Kazan, 2009;Gillmor et al, 2010Gillmor et al, , 2014Ito et al, 2011;Xu and Li, 2011;C ßevik et al, 2012;Rai et al, 2014;Yang et al, 2014;Zhang et al, 2014;Raya-Gonz alez et al, 2014. However, how MED subunits could be interacting to determine the MED functioning per se on plant development remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it would be interesting to study the conservation and diversification of phytohormone mediated regulation of miR166/165, its target HD-ZIP IIIs across the plant species. Since both nutrient availability and phytohormones are known to regulate both miRNA expression and root development, it raises the possibility of regulation of these miRNAs through nutrient-phytohormone crosstalk, which remains an interesting area to be addressed 1, 41 .
Figure 7A hypothetical model showing complex crosstalk among phytohormones, miR166/165, HD-ZIP IIIs and KAN genes regulating root growth. miR166/165 and HD-ZIP IIIs mediated root growth and development is regulated by various hormones such as IAA (red lines), GA (green lines), CK (grey lines), ABA (purple lines), JA (blue lines) and SA (orange lines) through transcriptional regulation of miR166/165, HD-ZIP IIIs and KAN genes.
…”
Section: Discussionmentioning
confidence: 99%
“…According to this view, ethylene, besides P and Fe deficiency responses, is also implicated in the induction of responses to K deficiency [138], to S deficiency [139,140], and to other deficiencies ( [3] and references therein). Recently, Rai et al [141] demonstrated the potential roles of auxin and Zinc (Zn) in mediating local Pi deficiency responses of the root system during growth under different Fe regimes, supporting the existence of crosstalk between Pi, Fe and Zn for maintaining Pi homeostasis.…”
Section: Crosstalk Among Fe and P Deficienciesmentioning
confidence: 99%